PENGEMBANGAN LKS KIMIA BERBASIS MEDIA GRAFIS JENIS KOMIK PADA MATERI LARUTAN PENYANGGA - Lisa, Lisa; Hairida, Hairida; Masriani, Masriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe aims of this study were to determine the level of feasibility of chemistry student worksheet based comic graphic media was developed based on expert judgement and the level of readability based on field trial. The form of this study was research and development that adopted Borg and Gall?s development model. The subject of this study was chemistry student worksheet based comic graphic media which was tried on 9 students of SMAN 10 Pontianak in preliminary trial and 36 students of SMAN 4, 8, and 10 Pontianak in field trial. Data collection instruments which is used are questionnaire of feasibility and questionnaire of students response. The result of processing data shows that chemistry student worksheet was developed feasible to be used in learning, it was reviewed from percentage of content feasibility was of 90,55%, presentation feasibility was of 91,84%, language feasibility was of 76,67%, and graphic feasibility was of 81,54%. Based on calculation of the percentage of student questionnaire response, the level of readability in preliminary trial was of 80,17% and field trial was of 75,96%. It showed that the level of chemistry student worksheet based comic graphic media belongs to high criteria. Keywords: student worksheet, graphic media, feasibility, readability, buffer solution